PEMODELAN DATAWAREHOUSE KOPERASI DENGAN METODE FOUR-STEP KIMBALL - Dony Oscar (Jurnal Teknik Informatika, 2015)
Abstract - As an institution that has an objective to help the welfare of its members, Cooperative Employees would require an accountability report as one of support for the Board to conduct the evaluation, planning, and provide flexibility for the board to make decisions. But the information systems used today can not meet these needs, because the information system used currently only able to produce a report transaction data reports on the members. This study aimed to explore whether the data warehouse model as the most appropriate to be used by the Board to analyze any existing data so that the information can be utilized as a support in any decision making process. By using a four-step method kimball will build a data warehouse that will present the report in the form mutidimensi useful for the Board to conduct in-depth analysis to improve the quality of decisions made. Results from this study is a data warehouse model and its application to assist the cooperative management in analyzing the existing data information as the basis for each decision made.